Potential Application of Electronic Road Pricing (ERP) on Bandung City Roads - Hammam, M Najwan; O R, M Achdiat; Nurwidya A, Oshi; Novriani, Shinta (Riviera Publishing, 2024)
This research investigates the potential implementation of Electronic Road Pricing (ERP) in Bandung City, Indonesia, focusing on its effectiveness in reducing traffic congestion. The study employs a quantitative approach using a survey method, experiments, and statistical analyses to evaluate ERP's impact on road traffic performance and cost efficiency. The research design includes traffic volume analysis, vehicle operating costs, and data collection through questionnaires from Bandung residents selected randomly. The research subjects include frequent road users in congested areas, and the study was conducted in 2023. Using binary logistic regression, the results show significant shifts in road user behavior, with reductions in traffic volumes of 33% on Jalan Sukajadi, 38% on Jalan Dr. Djunjunan, and 23% on Jalan Terusan Jakarta. Additionally, ERP was found to improve cost efficiency in traffic management. The study concludes that ERP is a promising solution for managing congestion in Bandung, with broader implications for other congested cities in Indonesia.